A COMBINED EFFECT OF DEXTROMETHORPHAN AND MELATONIN ON NEUROPATHIC PAIN BEHAVIOR IN RATS - Wang, Shuxing (2009)
Previous study has shown that administration of melatonin into the anterior cingulate cortex contralateral to peripheral nerve injury prevented exacerbation of mechanical allodynia with a concurrent improvement of depression-like behavior in Wistar-Kyoto (WKY) rats, a genetic variation of Wistar rats. In the present study, we examined the effect of the individual versus combined treatment of melatonin and/or dextromethorphan (DM), a clinically available N-methyl-D-aspartate (NMDA) receptor antagonist, on pain behaviors in WKY rats with chronic constriction sciatic nerve injury (CCI). Pain behaviors (thermal hyperalgesia and mechanical allodynia) were established at one week after CCI. WKY rats were then treated intraperitoneally with various doses of melatonin, DM or their combination once daily for the following week. At the end of this one-week treatment, behavioral tests were repeated in these same rats. While DM alone was effective in reducing thermal hyperalgesia at three tested doses (15, 30 or 60 mg/kg), it reduced mechanical allodynia only at high doses (30 or 60 mg/kg). By comparison, administration of melatonin alone was effective in reducing thermal hyperalgesia only at the highest dose (120 mg/kg, but not 30 or 60 mg/kg) tested in this experiment. Melatonin alone failed to reverse allodynia at all three tested doses (30, 60 and 120 mg/kg). However, the combined intraperitoneal administration of melatonin (30 mg/kg) and DM (15 mg/kg) effectively reversed both thermal hyperalgesia and mechanical allodynia although each individual dose alone did not reduce pain behaviors. These results suggest that a combination of melatonin with a clinically available NMDA receptor antagonist might be more effective than either drug alone for the treatment of neuropathic pain.